Big Nate : In the Zone : Big Nate Novels #6 - Peirce, Lincoln (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2014)
Stuck in a rut of bad luck, Nate Wright gets a boost from Chad's lucky foot and suddenly, good luck is everywhere he turns.
Chiefly illustrations.
Keywords: Schools -- Fiction; Luck -- Fiction; Fate and fatalism -- Fiction; School stories; Graphic novels